Performance analysis of turbo codes over Rician fading channels with impulsive noise - Ali, Syed Amjad; Ince, Ethan AliRiza (IEEE, 2007)
The statistical characteristics of impulsive noise differ greatly from those of Gaussian noise. Hence, the performance of conventional decoders, optimized for additive white Gaussian noise (AWGN) channels is not promising in non-Gaussian environments. In order to achieve improved performance in impulsive environments the decoder structure needs to be modified in accordance with the impulsive noise model. This paper provides performance analysis of turbo codes over fully interleaved Rician fading channels with Middleton's additive white Class-A impulsive noise (MAWCAIN). Simulation results for the memoryless Rician fading channels using coherent BPSK signaling for both the cases of ideal channel state information (ICSI) and no channel state information (NCSI) at the decoder are provided. An eight state turbo encoder having (1, 13/15, 13/15) generator polynomial is used throughout the analysis. The novelty of this work lies in the fact that this is an initial attempt to provide a detailed analysis of turbo codes over Rician fading channels with impulsive noise rather than AWGN.
IEEE International Conference on Telecommunications/IEEE Malaysia International Conference on Communications (ICT-MICC 2007) -- MAY 14-17, 2007 -- Penang, MALAYSIA
Keywords: channel reliability; ideal channel state information; Middleton's additive white Class-A impulsive noise channel; no channel state information; Rician fading channel; turbo codes